Sustainable Sports Events and Musculoskeletal Health: A Review of the Orthopedic Impact of Strategies to Reduce the Carbon Footprint - Jácome, Gabriel Omar León; Castro, Oscar; Castro, PhD (c) Eugenio (Journal of Posthumanism, 2025)
The organization of sustainable sporting events has become relevant in the context of climate change and health promotion. However, the implementation of strategies to reduce the carbon footprint can have direct or indirect implications on the musculoskeletal health of athletes, workers and attendees. This review examines the orthopedic impact of such strategies, analyzing how green transportation, temporary reusable infrastructure, and the use of sustainable materials influence musculoskeletal injuries. We identified 28 studies between 2019 and 2024 that evaluate the relationship between sustainability in sporting events and orthopedic health. It is concluded that, although sustainable strategies have multiple environmental and economic benefits, they must be integrated with injury prevention measures and ergonomic design to preserve musculoskeletal health.